Developing a Flipping Book-Based E-Book to Enhance Learning Outcomes in Basic Skin Care for Vocational Education - Anggraeni, Nelly Setyowati; Ihsani, Ade Novi Nurul; Handayani, Sri; Qudus, Nur; Wahyuningsih, Sri Endah; Apriyani, Delta (Universitas Negeri Semarang, 2025)
The increasing demand for digital integration in vocational education requires innovative learning media that enhance engagement and achievement. This study aimed to develop a Flipping Book-based e-book as an interactive learning tool for the Basic Skin Care course in vocational high school settings. Utilizing a Research and Development (R&D) approach with the ADDIE model, the study involved 60 tenth-grade students divided into experimental and control groups. Validation results by material and media experts showed high feasibility, with average validity scores of 0.924 and 0.935, respectively. Practicality testing also indicated excellent usability, with a practicality score of 93%. Effectiveness was tested through an independent sample t-test, revealing a significant improvement in the experimental group compared to the control group (p < 0.05). The N-Gain analysis showed a moderate learning improvement (0.61) for the experimental group and a low improvement (0.15) for the control group. These findings confirm that the Flipping Book-based e-book effectively enhances student learning outcomes in vocational education, particularly skill-oriented courses like Basic Skin Care. Future research is recommended to expand the application of similar interactive e-learning innovations across other vocational disciplines.